(untitled) (Trabalho & Educação, 2016)
As part of a doctoral research, this article aims to contribute to the construction of the of invested knowledge notion, developed by the Department of Ergology. It is considered that the activity is even the movement of the genesis of knowledge; calls the notion of activity, consciousness and memory, philosophy of life and theory of relationship with knowledge. It is argued that this knowledge is not always revealed to the body-itself, it can also be unconscious for this needs to be recovered to be placed in relation to the knowledge set up to be accessed by others, which will give it the status of academic knowledge. States that constituted knowledge is always provisional because it is always in gap with the knowledge invested in the body-itself by the activity. It concludes with the formulation of a problem of the "Know Invested" because when one know has just been systematized or achieve the status of constituted knowledge it triggers internal processes that will generate other invested knowledge, successively. ___ No quadro de uma pesquisa de doutorado, este artigo se propõe a colaborar para a construção da noção de saber investido, desenvolvida pelo Departamento de Ergologia. Considera-se que a atividade é mesmo o movimento da gênese do saber, convoca a noção de atividade, de consciência e memória, a filosofia da vida e a teoria da relação com o saber. Argumenta-se que esse saber nem sempre é revelado ao corpo-si, pois pode ser também inconsciente, por isto necessita ser recuperado para ser colocado em relação com os saberes constituídos para ser acessado por outras pessoas, que lhe conferirão o estatuto de saber acadêmico. Afirma que o saber constituído é sempre provisório porque ele sempre está em defasagem em relação ao saber investido no corpo-si pela atividade. Termina-se com a formulação de uma problemática do "Saber Investido", pois, quando um saber acaba de ser sistematizado ou atingir o status de saber constituído, ele desencadeia processos internos que irão gerar outros saberes investidos, assim sucessivamente.